Two new species and new records of Maruina Müller, 1895 (Diptera: Psychodidae) in Brazil - Bravo, Freddy; Araújo, Maíra Xavier (Zootaxa, 2018)
Two new species of Maruina, Maruina cirrata sp. nov. and Maruina mucugensis sp. nov., collected in two mountainous areas in Bahia, are described and figured. Additionally, we present new records of Maruina guria Bravo, 2004 and M. menina Bravo & Lago, 2003 in Brazil.